Cytosolic Free N-Glycans Are Retro-Transported Into the Endoplasmic Reticulum in Plant Cells - Katsube, Makoto; Ebara, Natsuki; Maeda, Megumi; Kimura, Yoshinobu (Frontiers in Plant Science, 2021)
During endoplasmic reticulum (ER)-associated degradation, free N-glycans (FNGs) are produced from misfolded nascent glycoproteins via the combination of the cytosolic peptide N-glycanase (cPNGase) and endo-β-N-acetylglucosaminidase (ENGase) in the plant cytosol. The resulting high-mannose type (HMT)-FNGs, which carry one GlcNAc residue at the reducing end (GN1-FNGs), are ubiquitously found in developing plant cells. In a previous study, we found that HMT-FNGs assisted in protein folding and inhibited β-amyloid fibril formation, suggesting a possible biofunction of FNGs involved in the protein folding system. However, whether these HMT-FNGs occur in the ER, an organelle involved in protein folding, remained unclear. On the contrary, we also reported the presence of plant complex type (PCT)-GN1-FNGs, which carry the Lewisa epitope at the non-reducing end, indicating that these FNGs had been fully processed in the Golgi apparatus. Since plant ENGase was active toward HMT-N-glycans but not PCT-N-glycans that carry β1-2xylosyl and/or α1-3 fucosyl residue(s), these PCT-GN1-FNGs did not appear to be produced from fully processed glycoproteins that harbored PCT-N-glycans via ENGase activity. Interestingly, PCT-GN1-FNGs were found in the extracellular space, suggesting that HMT-GN1-FNGs formed in the cytosol might be transported back to the ER and processed in the Golgi apparatus through the protein secretion pathway. As the first step in elucidating the production mechanism of PCT-GN1-FNGs, we analyzed the structures of free oligosaccharides in plant microsomes and proved that HMT-FNGs (Man9-7GlcNAc1 and Man9-8GlcNAc2) could be found in microsomes, which almost consist of the ER compartments.